Tathbiq al-Wasa'il al-Muta'addidah al-Tafa'uliyyah 'Abra Genially fi Ta'lim an-Nahwi li-Saff ath-Thani bi-Ma'had al-'Asri Miftah al-'Ulum - Rahmawati, Fitra Awaliya; Hidayati, Laily Nur (UAS PRESS, 2025)
Nahwu is a crucial branch of Arabic grammar essential for understanding the language's meaning. At the International Muhammadiyah Boarding School (IMBS) Miftahul Ulum Pekajangan, traditional teaching methods without interactive illustrations often result in student boredom and difficulty in comprehension. This study explores the impact of interactive media based on Genially on the nahwu learning outcomes of second-grade students in the 2024–2025 academic year. A quasi-experimental design with a nonequivalent control group approach was used, involving 56 students divided into control and experimental groups. Data were collected through tests and interviews and analyzed using the Mann-Whitney U-test. Results show a significant effect, with the experimental group's post-test mean score of 83.21 compared to the control group's 66.96 (Sig. 2-tailed = 0.004). These findings indicate that Genially-based interactive media enhances students' learning outcomes. Teachers are encouraged to adopt interactive learning tools to improve students' engagement and understanding in nahwu lessons. Keywords: nahwu, interactive media, genially